Survey of the amphibians in “Fânațele Clujului – Copârșaie”, part of the “Dealurile Clujului de Est” (ROSCI0295) Natura 2000 protected area - Nándor ERŐS; Mónika IANCULESCU; Vivien-Beatrix KOCSIS; Ágnes SZŐCS; Tibor SOS (Studia Universitatis Babeș-Bolyai. Biologia)
As habitat loss poses challenge to conservation, it is becoming increasingly important to address questions about the extent to which connectivity between habitat patches is changing, and how this affects the local population of different species in these patches. The objective of our research was to monitor ponds and the pond-breeding amphibian species in a protected area. Therefore, we conducted day and night surveys, and compare the data collected in 2022 with the results of the latest available survey (2019), to simulate the patch occupancy of amphibian species over a 25-year timeframe. We found that combining the species occupancy data collected from both day and night surveys lead to higher patch occupancy values and higher number of registered individuals, compared to data collected only during daytime. The number of ponds decreased from 2019 to 2022, and further habitat loss could result in the disappearance of the local population if the area continues to dry out. Climate and landscape change could be major contributors to habitat loss in the future, therefore, in order to ensure the persistence of these local populations, we recommend the development of climate and habitat scenarios, and the planning of conservation measures based on these scenarios.